CALCULATION OF GROWTH OF SKELETON DENDRITES AT ALLOYS SOLIDIFICATION USING THEORY OF FRACTALS - Ju. A. Samojlovich; V. I. Timoshpolslkij (Литьë и металлургия, 2008)
The possibility of determination of dendritic crystals configuration is shown, what in combination with complex of equations of unsteady-state heat conduction and convective diffusion makes universal physical-mathematical basis, allowing to forecast the development of time and area of complex processes.